The Necessity of Regional Economic Integration: a Lesson for South Asia? - Khan, Md. Rajin Makhdum; Imam, Faizah (European Journal of Economics and Business Studies, 2017)
ASEAN and the European Union have showed this world the privileges regional economic integration provides the states. Although Greece and Italy might be the torchbearers of criticism against regional cooperation and integration, these two organizations tend to be some prime examples of necessity of regional economic integration. This dissertation thus focuses on the privileges and advantages that regional economic integration system and organizations deliver to the states aligned within. With the possible and crucial criticisms on mind, the discussion moves forward analyzing if this system is making the countries perform better economically and advance towards domestic development. The dissertation further intends to find out why the South Asian nations might need similar kind of cooperation and why these countries should act more sensible to make the economic integration possible. While remarking the recommendations, the discussion also draws the barriers and the problems that this region might face in order to integrate their economies or enhance their trades. The core argument of this dissertation therefore lies in analyzing the importance of regional economic integration and liberal economics in this modern world and if the South Asian countries need economic integration to develop their domestic economies. The recommendations are to provide the possible ways to run the process and the drawbacks portion mentions the difficulties and barriers to be faced whilst all of these countries ongoing strict policies. The argument tries to find out the significance of liberal economics and tribulation of realism in the contemporary world.
Keywords: ASEAN, EU, Liberal, Cooperation, Failure, Protectionism